Longitudinal trajectories of the overall and regional body composition between severe acute malnourished and well-nourished children of Rohingya refugee camps - Manir, Mohammad Zahidul; Huq, A. K. Obidul (Frontiers in Public Health, 2024)
Objectives The present study aimed to observe how body composition differs between severe acute malnutrition (SAM) (treated with ready-to-use therapeutic food, RUTF) and well-nourished children. Methods A longitudinal investigation was conducted among well-nourished and SAM children of 6-59 months in Rohingya refugee camps. These two groups (350 children in each group) of children were observed over 12 weeks and individual data were collected during admission, follow-up visits, and at the time of discharge. Anthropometric information was collected following standard procedures. The thicknesses of the biceps, triceps, subscapular, and supra iliac skinfolds were measured using a Herpenden-type skinfold caliper. Separate linear mixed models were conducted to assess associations of the independent variables (i.e., group and time) with each of the dependent variables (i.e., biceps, triceps, subscapular, supra-iliac skinfold thickness (ST), fat mass (FM), and fat-free mass (FFM)). Results Both in well-nourished and SAM children, the mean biceps, triceps, subscapular, and supra-iliac ST, FM, and FFM increased over the 12 weeks. The increase in biceps ST was significantly faster in the SAM children compared to the well-nourished children (difference in slope = 0.366 mm every four weeks; p < 0.001). The increment rate in triceps ST was also faster in the SAM children compared to the well-nourished children (difference in slope = 0.430 mm every four weeks; p < 0.001). Moreover, the pace of increase in subscapular (difference in slope = 0.027 mm every four weeks; p < 0.001), and supra-iliac (difference in slope = 0.211 mm every four weeks, p < 0.001) ST was also significantly higher in the SAM group. Similarly, the change in FM (difference in slope = 0.065 kg every four weeks, p < 0.001) and FFM (difference in slope = 0.152 kg every four weeks, p = 0.023) was also significantly faster in SAM children compared to the well-nourished children over the treatment period. Furthermore, the girls gained significantly higher triceps ST, subscapular ST, FM, and FFM compared to the boys. Conclusion The benefit of RUTF was evident from this longitudinal study in the recovery of FM and FFM contents among the SAM children of Rohingya refugee camps.